2012
DOI: 10.7498/aps.61.164209
|View full text |Cite
|
Sign up to set email alerts
|

Effective radius of curvature of truncated laser beams with amplitude modulation and phase fluctuation

Abstract: Usually, high-power laser beams are amplitude modulated and have phase fluctuations (PFs). The analytic formula of the effective radius R of curvature of truncated laser beams with amplitude modulations (AMs) and PFs propagating through atmospheric turbulence is derived by using the statistical optics method. It is shown that the R in free space increases with the increases of the phase fluctuation parameter, the intensity modulation parameter and the truncated parameter. And the influence of turbulence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Meanwhile, the practical optical systems mostly are equipped with limited apertures which usually cause the laser beams propagating through these systems truncated. Thus, based on the mathematics model proposed by Manes and Simmons, a series of works concerning the propagation properties have been accomplished, [19][20][21][22][23][24][25] including M 2 factor of truncated high-power laser beams passing through turbulent atmospheric and passing through optical system with an aperture. The results showed that the propagation properties of high-power laser beams are related to both amplitude modulations and phase fluctuations when passing through optical system with an aperture.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the practical optical systems mostly are equipped with limited apertures which usually cause the laser beams propagating through these systems truncated. Thus, based on the mathematics model proposed by Manes and Simmons, a series of works concerning the propagation properties have been accomplished, [19][20][21][22][23][24][25] including M 2 factor of truncated high-power laser beams passing through turbulent atmospheric and passing through optical system with an aperture. The results showed that the propagation properties of high-power laser beams are related to both amplitude modulations and phase fluctuations when passing through optical system with an aperture.…”
Section: Introductionmentioning
confidence: 99%